2020
DOI: 10.3390/ijms22010209
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Interaction of LVV-Hemorphin-7 with Angiotensin II Type 1 Receptor

Abstract: Hemorphins are known for their role in the control of blood pressure. Recently, we revealed the positive modulation of the angiotensin II (AngII) type 1 receptor (AT1R) by LVV-hemorphin-7 (LVV-H7) in human embryonic kidney (HEK293) cells. Here, we examined the molecular binding behavior of LVV-H7 on AT1R and its effect on AngII binding using a nanoluciferase-based bioluminescence resonance energy transfer (NanoBRET) assay in HEK293FT cells, as well as molecular docking and molecular dynamics (MD) studies. Satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Several studies have investigated this heteromer in a variety of systems, and reported evidence for it being a constitutive heteromer that displays modulated G protein signaling and β-arrestin recruitment [9,24,25]. To investigate this complex we first looked at binding of a BODIPY-630/650 tagged angiotensin II ligand (BODIPY-AngII) to the N-terminally Nluc-tagged AT 1 receptor (Nluc-AT 1 ; Figure 2a) using the NanoBRET ligand binding assay [18][19][20][21]. We were able to demonstrate saturable binding of BODIPY-AngII to the AT 1 receptor, which was substantially reduced by treatment with a high concentration of the AT 1 antagonist olmesartan (Figure 2b), enabling generation of a BODIPY-AngII specific binding curve (Figure 2c).…”
Section: At 1 -β 2 Ar Heteromermentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated this heteromer in a variety of systems, and reported evidence for it being a constitutive heteromer that displays modulated G protein signaling and β-arrestin recruitment [9,24,25]. To investigate this complex we first looked at binding of a BODIPY-630/650 tagged angiotensin II ligand (BODIPY-AngII) to the N-terminally Nluc-tagged AT 1 receptor (Nluc-AT 1 ; Figure 2a) using the NanoBRET ligand binding assay [18][19][20][21]. We were able to demonstrate saturable binding of BODIPY-AngII to the AT 1 receptor, which was substantially reduced by treatment with a high concentration of the AT 1 antagonist olmesartan (Figure 2b), enabling generation of a BODIPY-AngII specific binding curve (Figure 2c).…”
Section: At 1 -β 2 Ar Heteromermentioning
confidence: 99%
“…Recently, we have developed the NanoBRET ligand binding assay [18][19][20][21][22][23], in which we have successfully monitored binding of fluorescent ligands to Nanoluciferase (Nluc)tagged GPCRs. In the present study, we have demonstrated the Receptor-HIT assay utilizing NanoBRET ligand binding to investigate two GPCR heteromers: between the angiotensin II type 1 (AT 1 ) receptor and the β 2 adrenergic receptor (AT 1 -β 2 AR heteromer), as well as between the AT 1 and angiotensin II type 2 receptor (AT 1 -AT 2 heteromer).…”
Section: Introductionmentioning
confidence: 99%
“…The expressed receptor was the GPCR-type complex, involving recruitment of beta-arrestin upon stimulation, followed by the ligand binding, and an interesting conclusion was drawn concerning the role of hemorphins in analgesia. This group also examined the binding behavior of LVV-H7 to AT1R and its effect on angiotensin II binding using nanoluciferasebased bioluminescence resonance energy transfer (NanoBRET) in HEK293FT cells [54].…”
Section: Other Techniquesmentioning
confidence: 99%
“…It was shown that camel LVV-H7 produced stronger interactions with all studied proteins (MOR, ACE and IRAP) than non-camel LVV-H7. A year later, Ali et al presented application of molecular docking to investigate binding of LVV-H7 to AT1R receptor [54]. It was reported that the performed interaction indicates that docking mechanism of LVV-H7 to angiotensin II type 1 receptor (AT1R) allosterically potentiates angiotensin II binding.…”
Section: Other Techniquesmentioning
confidence: 99%
See 1 more Smart Citation